Isaria fumosorosea and Metarhizium anisopliae for controlling Atteva sciodoxa (Lepidoptera: Yponomeutidae), a pest of Eurycoma longifolia - Sajap, Ahmad Said; Zahari, Rozihawati; Omar, Dzolkhifli; Lau, Wei Hong (Forest Research Institute Malaysia, 2014)
Tiger moth, Atteva sciodoxa (Lepidoptera: Yponomeutidae), is a major pest of tongkat ali, Eurycoma longifolia (Simaroubaceae). To find a safe and effective method for controlling the pest, two indigenous entomopathogenic fungi, Isaria fumosorosea and Metarhizium anisopliae, isolated from bagworms Pteroma pendula (Lepidoptera: Psychidae), were bioassayed against the pest. The larvae were separately sprayed with concentrations of 1 × 102 to 1 × 105 conidia mL-1 of each fungal isolate. Both fungi were pathogenic to third instar larvae of A. sciodoxa. However, M. anisopliae was more virulent than I. fumosorosea. The median effective concentrations for M. anisopliae and I. fumosorosea were 4.23 × 10 3 and 8.24 × 104 conidia mL-1 respectively. The median infective times ranged from 4.3 to 10.3 days for M. anisopliae and 7.6 to 16.3 days for I. fumosorosea. Metarhizium anisopliae killed 48 to 88% larvae while I. fumosorosea, 26 to 62% larvae for the lowest and highest concentrations respectively, 10 days after treatment. Spraying of M. anisopliae at 2 × 107 conidial mL-1 suspension reduced the population of A. sciodoxa attacking 2-year-old saplings up to 89%, 7 days after treatment. This study indicates the potential of M. anisopliae for controlling A. sciodoxa.